A Comparison of the Response and Voltage Regulation Performance of the Single-Channel DC/DC Boost Converter Circuit with Artificial Neural Networks, Fuzzy Logic and PID Controllers - Arckarakit Chaithanakulwat; Nuttee Thungsuk; Teerawut Savangboon; Somchai Ngao-Ngam; Phatcharaphong Kanharin; Nikom Kanjak; Thaweesak Tanaram (My University, 2023)
Fixed-speed wind turbines for generating electricity are also important because they are clean energy and do not pollute the environment.Developing maximum wind energy tracking and increasing DC voltage to optimal values is also an important factor designers must consider so that the power from generators connected to wind turbines can function efficiently.Therefore, in this researcher paper proposed a single-channel dc/dc boost converter control, three forms of algorithms consisting of neural networks, fuzzy algorithms and PID algorithms.The purpose of bringing these algorithms controlled because they wanted to compare the response and voltage control performance of the single-channel DC/DC boost converter to be associated with a three-phase inverter that controls PWM signal modulation with space vector technique.However, the principles and methodologies in this article are presented to simulate the algorithmic response using the MATLAB/Simulink program and compare it with the prototype mechanism.A comparison of the response performance and voltage regulation of the single-channel DC/DC boost converter showed that the three algorithms have different advantages and disadvantages but can be used together to achieve high efficiency.
Keywords: Advanced DC-DC Converters